Influencia de la cascarilla de cacao y edulcorante natural en el contenido de polifenoles totales y capacidad antioxidante de una infusión - Rey Tobar, Génesis Michelle (2022)
The objective of this study was to evaluate the influence of the relationship between cocoa husk (Theobroma cacao L.) and natural sweetener on the total polyphenol content and antioxidant capacity of an infusion. The factor under study was: relationship between percentages of cocoa husk (80%, 83%, 86%, 89%,92%, 95%) with percentage of natural sweetener (20%, 17%, 14%, 11%, 8%, 5%). A Completely Random Design (DCA) was applied with six treatments and three repetitions each. 162 g of cocoa husk and natural sweetener were used as experimental unit, which were combined and packed in filter bags (1.5 g). The physicochemical components evaluated were moisture and ashes to the raw material, functional characteristics and sensory analysis were also evaluated. In addition, it determined the content of total polyphenols and antioxidant capacity. The results found showed that T6 (95% Theobroma cacao L. husk and 5% natural sweetener presented a content of 36,2000 mg GAE / 100g and 384.9633 ABTS respectively. In addition, an organoleptic evaluation was carried out with 80 judges classified as untrained judges where the product was rated according to the attribute of their preference, the infusion formulation that achieved greater acceptance by the panelists was T2 (83% of Theobroma husk cacao L. and 17% natural sweetener with 28% acceptability.